PENERAPAN DISCOVERY LEARNING BERBANTUAN MEDIA GEOBOARD UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERSEGI DAN PERSEGI PANJANG KELAS III SD - Dwi Pramesti, Nabela; Fahriza Fuadiah, Nyiayu; Surmilasari, Nora (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Understanding the concepts of squares and rectangles refers to students’ ability to identify, explain, distinguish, and apply the properties of these two plane figures in mathematical problem solving. This study aimed to determine the improvement of third-grade elementary school students’ conceptual understanding through the implementation of the Discovery Learning model assisted by Geoboard media. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest–Posttest Design. The sample consisted of 29 students of class IIIA at SD Negeri 101 Palembang selected through purposive sampling. Data were collected through conceptual understanding tests in the form of pretest and posttest, as well as documentation. The results showed that the mean pretest score of 70.3 increased to 87.5 in the posttest. The Paired Sample t-Test yielded a significance value of 0.000 (< 0.05), indicating a significant effect after the treatment. In addition, the average N-Gain score of 0.5674 was categorized as moderate. Therefore, the implementation of the Discovery Learning model assisted by Geoboard media was effective in improving students’ understanding of square and rectangle concepts.